Beauty as Gendered Inequality - Sarpila, Outi; Brans, Luuc; Kuipers, Giselinde (Springer, 2026)
Gender is one of the most common perspectives through which the relation between beauty and inequality is studied. Recently, as our academic understanding of gender and gender systems in society shifts, academics are rethinking the triangular relation between beauty, inequality, and gender. Against this backdrop, this chapter discusses how beauty and appearance are gendered, and how this is related to inequalities of gender and beyond. We examine the gendered nature of beauty, highlighting beauty standards, beauty practices, and the social norms surrounding them. After, we discuss unequal gender outcomes of beauty/appearance, and the mechanisms suggested to explain them. Finally, we ask what might be lost or overlooked in current approaches that often take on a binary gender perspective. We suggest that future research can break new ground by paying more explicit and critical attention to the shifting gender systems (and the resistance this sparks), by analyzing beauty and gender in intersectional terms, and by going beyond the gender binary.
Handbook of Beauty and Inequality